2021
DOI: 10.1556/063.2021.00047
|View full text |Cite
|
Sign up to set email alerts
|

Scrutinizing Algerian EFL students’ challenges in research teaching and writing

Abstract: Writing to report research writing may be a daunting task since it requires motivation, interest, background knowledge and hard work from the part of students. This paper focused on the major obstacles faced by the English foreign language learners in research writing at Belhadj Bouchaib University, Algeria, in addition to the teachers’ attitudes towards their students’ work. The study relied on a triangulated approach which enclosed quantitative and qualitative methods and its importance lied in providing ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Backing in this study of Hamzaoui (2021) for the first data of poor education and deficiency in methodology are that students were taught methodology only by a parttime teacher who may not have taught them well, and that the students encountered the following challenges in research writing: distinguishing between formal and nonformal academic writing, selecting appropriate words to convey ideas, grammar, textual organization, paraphrasing and summarizing authors' ideas, writing a literature review and selecting the sample of the research, dissatisfaction with the teaching from courses and subjects in their programs.…”
Section: Study No 9 (Algeria)mentioning
confidence: 84%
See 1 more Smart Citation
“…Backing in this study of Hamzaoui (2021) for the first data of poor education and deficiency in methodology are that students were taught methodology only by a parttime teacher who may not have taught them well, and that the students encountered the following challenges in research writing: distinguishing between formal and nonformal academic writing, selecting appropriate words to convey ideas, grammar, textual organization, paraphrasing and summarizing authors' ideas, writing a literature review and selecting the sample of the research, dissatisfaction with the teaching from courses and subjects in their programs.…”
Section: Study No 9 (Algeria)mentioning
confidence: 84%
“…Data were gathered by Hamzaoui (2021) in this study from thirty (30) Master two level students and six (6) teachers in a Department of English at a university in Algeria. The only claim of this study is that Algerian EFL students lack proficiency in research writing because they are not knowledgeable of the significance of research and are not prepared well for it.…”
Section: Study No 9 (Algeria)mentioning
confidence: 99%
“…Writing strong academic paragraphs in English requires the writer to have a strong command of the language and an understanding of the structure of its content because they need to fulfill a number of distinct but related tasks such as gathering and ordering content, shaping content into correct and clear expressions, and meeting the genre requirements of the writing (Mahmud & Rahman, 2023). However, achieving cohesivity and ensuring that their writing is syntactically developed proves to be a problem (Harris et al, 2017;Ruscetti et al, 2018;Hamzaoui, 2021), as they face writing difficulties in major aspects of writing in English, such as their lack of vocabulary and understanding of grammar, lack of knowledge on the mechanics of writing (Ferguson et al, 2011;Singh, 2017;Phuong, 2021), the studies' organisation Hanauer & Englander (2013); Komba (2015); Mahammoda (2016); Flowerdew (2019), and genre conventions (Bitchener & Basturkmen, 2006;Kao & Reynolds, 2017;Finn, 2018). The errors in identifying appropriate content for their research article would cause the students to either exaggerate or underplay the big claims of their topic and the significance of their study.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Students' writing for final assignments and research encounter obstacles caused by psychological (Anas, 2021), lingual (Tiwari, 2019), and technological factors (Alamri, 2021). Most students have insufficient skills in expressing and constructing ideas into words, finding supporting resources, and using writing tools (Hamzaoui, 2021). Previous studies examined the difficulties students face when writing for academic purposes and suggested some strategies to overcome these challenges.…”
Section: Introductionmentioning
confidence: 99%